Groundwater quality assessment in different volcanic rocks using water quality index in the tropical area, Indonesia - Hendrayana, Heru; Riyanto, Indra Agus; Ismayuni, Novia; Nuha, Azmin; Muhammad, Azwar Satrya; Fadillah, Arif (Brawijaya University, 2024)
Groundwater is the main water source that is most widely used in the world, one of which is in Indonesia. One of the uses of groundwater is for consumption needs. Therefore, the groundwater used should have good water quality. For this reason, this study aimed to determine groundwater quality in Indonesia during the dry season and make recommendations for groundwater management policies. A total of 211 groundwater samples taken from springs, drilled wells, and dug wells spread across volcanic areas on the islands of Sumatra, Java, Bali, and Sulawesi were collected to test their quality in this research. The method used in this research consisted of 4 analyses: WHO threshold analysis, Piper Diagram, Water Quality Index (WQI), and statistical correlation and regression. Based on the analysis, it was discovered that 47 K+ samples, 1 Na+ sample, 5 Ca2+ samples, 1 Cl- sample, 115 HCO3- samples, 3 TDS samples, and 3 pH samples exceeded WHO standards. The results of the Piper triangle diagram analysis showed that the majority of groundwater in Indonesia falls into the Unpolluted Groundwater classification (categories D and G), and the results of the WQI analysis also showed that 98% of the groundwater in Indonesia analyzed falls into the excellent and good water categories. The results of statistical analysis of the parameters K+, Na+, Mg2+, Ca2+, SO42-, Cl-, HCO3-, TDS, and pH showed that all these parameters are strongly and positively correlated with the WQI value.